2022
DOI: 10.2147/ijgm.s357552
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Hospitalized COVID-19 Patients in the Four Southern Regions Under the Proposed Southern Business Unit of Saudi Arabia

Abstract: Background This is the first descriptive and comparative study conducted of COVID-19 inpatients from multi-centers in the four administrative southern regions and proposed Southern Business Unit (Jazan, Najran, Bisha, and Aseer) of the Kingdom of Saudi Arabia (KSA). Methods Participants were 809 randomly selected patients admitted to the eight sampled hospitals with confirmed COVID-19 between March 2020 and February 2021. We assessed and compared socio-demographics, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
0
0
2
Order By: Relevance
“…While studies have documented the challenges inherent in measuring quality through healthcare utilization rates [18], multiple studies have attempted to address the variation in healthcare service quality across different countries, cities, and hospitals [21,[37][38][39]. This study found variations in the acceptance rate of medical emergency e-referral requests across different Ministry of Health BUs, with higher acceptance rates found in the Northern BU, as compared to the central unit, a finding that is consistent with previous studies measuring quality variation during the coronavirus disease 2019 (COVID-19_ pandemic [17][18][19]40]. These results indicate that the Northern region may have a greater need for improved infrastructure to alleviate resource constraints and address higher demand.…”
Section: Discussionsupporting
confidence: 86%
“…While studies have documented the challenges inherent in measuring quality through healthcare utilization rates [18], multiple studies have attempted to address the variation in healthcare service quality across different countries, cities, and hospitals [21,[37][38][39]. This study found variations in the acceptance rate of medical emergency e-referral requests across different Ministry of Health BUs, with higher acceptance rates found in the Northern BU, as compared to the central unit, a finding that is consistent with previous studies measuring quality variation during the coronavirus disease 2019 (COVID-19_ pandemic [17][18][19]40]. These results indicate that the Northern region may have a greater need for improved infrastructure to alleviate resource constraints and address higher demand.…”
Section: Discussionsupporting
confidence: 86%
“…tahun 2022 menemukan dari 809 pasien yang dirawat di sebuah rumah sakit di Arab Saudi, ratarata berusia 60 tahun dengan komorbid paling banyak yang dimiliki pasien adalah diabetes, hipertensi, obesitas, dan penyakit jantung. 27 Rata-rata lama rawat inap pasien pada penelitian tersebut adalah 11 hari.B Penelitian tersebut juga menemukan bahwa pasien dengan faktor resiko yaitu usia tua dan komorbid memiliki resiko lebih tinggi untuk mengalami komplikasi, masuk ke ruang ICU, dan mortalitas. 27 Pada penelitian ini, jumlah wanita lebih banyak dibandingkan laki-laki.…”
Section: Hasil Penelitian Dan Pembahasanunclassified
“…27 Rata-rata lama rawat inap pasien pada penelitian tersebut adalah 11 hari.B Penelitian tersebut juga menemukan bahwa pasien dengan faktor resiko yaitu usia tua dan komorbid memiliki resiko lebih tinggi untuk mengalami komplikasi, masuk ke ruang ICU, dan mortalitas. 27 Pada penelitian ini, jumlah wanita lebih banyak dibandingkan laki-laki. Hal tersebut berbeda dengan penelitian Karyono dan Wicaksana yang menyebutkan bahwa jenis kelamin laki-laki (54,6%) memiliki proporsi yang lebih banyak.…”
Section: Hasil Penelitian Dan Pembahasanunclassified